Multiwavelength Properties Of Selected High Redshift Blazars - Harutyunyan, G. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
High-redshift blazars detected in the y-ray band are the most powerful steady objects in the universe. Multiwavelength observations of these distant objects are of particular interest as they can help to understand the y -ray evolution of blazars as well as the formation and propagation of relativistic jets in the early epochs of the Universe. Блазары с большим красным смещением, обнаруженные в y-диапазоне, являются самыми мощными устойчивыми объектами во Вселенной. Многоволновые наблюдения за этими далекими объектами особенно интересны, так как они могут помочь понять эволюцию y-излучения блазаров, а также формирование и распространение релятивистских струй в ранние эпохи Вселенной.
Keywords: Astrophysics